Ultrafast laser cutting of transparent materials: the trend towards tailored edges and curved surfaces - Flamm, Daniel; Kleiner, Jonas; Kaiser, Myriam; Zimmermann, Felix; Großmann, Daniel Günther; Kumkar, Malte (SPIE, 2021)
We report on ultrashort pulsed laser fabrication strategies for glass articles with customized edges and curved surfaces. To achieve single-pass, full-thickness modifications along the entire substrate processing optics are presented that allows for beam shaping of non-diffracting beams and, additionally, for aberration compensation of phase distortions occurring at the tilted or curved interfaces. The efficacy of our concepts is presented by evaluating the surface and edge qualities of separated glass tubes with complex inner and outer contours as well as glass chamfer structures.